Environmental risk assessment of genetically modified organisms. (CABI, 2004)
Many international fora have identified the need for comprehensive, transparent, scientific methods for the pre-release testing and post-release monitoring of transgenic plants to ensure their environmental safety and sustainable use. There is also wide recognition that the regulatory and scientific capacity for conducting assessments needs to be strengthened worldwide. This book presents a case study of Bt maize in Kenya, highlighting the various strategies for the assessment and management of environmental risks associated with the establishment of transgenic plants in the country.